Scanning Electron Microscopic Study on Oviduct of Goat during Luteal Phase of Estrous Cycle - Monali B. Bhesaniya; Vishnudeo Kumar; Anil Sharma; Shivaji H. Talekar; Arun Kumar Sharma (Indian Journal of Veterinary Anatomy, 2024)
Present study was carried out to investigate the scanning electron microscopic characteristics of oviduct of goats during luteal phase of the estrous cycle. The samples of oviduct of 10 adult goats were collected from abattoir, after examining the status of ovaries. The collected samples were processed by standard protocol for scanning electron microscopy. Study revealed that the presence of mucosal folds lined with ciliated and non- ciliated or secretory cells in all three segments (infundibulum, ampulla and isthmus) of the oviduct. Numerous secretory cells having secretory blebs were noticed in infundibulum and ampulla. Non-ciliated cells possessed microvilli with varied length on their apical surfaces during luteal phase. Ampullary region in the luteal phase showed more number of secretory cells similar to infundibulum. The isthmus part showed less number of ciliated cells which were unevenly distributed with non-ciliated cells.